The effect of 12 weeks of Pilates exercises on ghrelin serum level and appetite in women with type 2 diabetes - Azam Talebi; Elham Eftekhari Ghinani; Jamshid Banaei Borujeni; Saeed Keshavarz (Mashhad University of Medical Sciences, 2024)
Introduction: An increase in appetite and lack of enough movement accelerates the process of contracting chronic diseases, including diabetes, so the present study was conducted with aim to investigate the effect of 12 weeks of Pilates exercises on ghrelin serum levels and appetite in women with type 2 diabetes.Methods: This experimental study was conducted on women with type 2 diabetes (from the Najafabad Diabetes Association) with an age range of 35 to 55 years in Najafabad city. People were randomly divided into experimental and control groups. The first group performed Pilates exercises for 12 weeks incrementally, 3 sessions a week and each session lasted 50 minutes, and for the control group who continued the routine life program, before and after the implementation of the exercise protocol, blood was taken and ghrelin was measured by Eliza method. Data was analyzed by SPSS software (version 22) and Mann-Whitney test. P<0.05 was considered statistically significant.Results: The result showed that performing 12 weeks of Pilates exercises was significant on the serum level of ghrelin (P≤0.001), feelings of hunger (P≤0.001), feelings of fullness (P≤0.001), feelings of satiety (P≤0.001) and feeling of desire for food (P≤0.001) in women with type 2 diabetes.Conclusion: Pilates exercises can improve the serum level of ghrelin and appetite, therefore Pilates exercises may be an effective treatment method for women with type 2 diabetes.